Dielectric response of 1, 1-difluorosumanene caused by an in-plane motion. (19th April 2022) - Li, Minghong; Wu, JianYun; Sambe, Kohei; Yakiyama, Yumi; Akutagawa, Tomoyuki; Kajitani, Takashi; Fukushima, Takanori; Matsuda, Kazunari; Sakurai, Hidehiro
Abstract : A large dipole moment of 1, 1-difluorosumanene realized a 120° in-plane pendulum motion in the stacking columns at above 380 K. This dynamic motion in the solid state enabled anisotropic dielectric relaxation induced by the external electric field. Abstract : We have designed and synthesized a new curved π-conjugated molecule, 1, 1-difluorosumanene (1 ), which possesses two fluorine atoms on the same benzylic carbon of unsubstituted sumanene, producing a large dipole moment along the in-plane direction. Thermal analyses, variable-temperature X-ray diffraction, and IR measurements indicated a 120° in-plane motion of 1 in the stacking columns, which did not cause any phase transition in the crystalline state. Indeed, dielectric measurements on powder and single-crystal forms of 1 showed that both the real ( ε 1 ) and imaginary ( ε 2 ) parts of the dielectric constant were enhanced above ∼360 K at 1 MHz with a Debye-type dielectric relaxation, confirming that 1 underwent a pendulum fluctuation induced by the external electric field.